Análisis de inconformidades que generaron reclamos en los procesos de cotización de obras en contratación pública de la zona 3 - Fuenmayor Muñoz, Katherine Patricia (2023)
Public procurement refers to the management of public resources, in Ecuador since 2008 there was a new regulatory and institutional framework. The objectives of public contracting and quotation processes are to achieve transparency and compliance with the basic principles of contracting processes and their effectiveness. The present research project aims to analyze non-conformities that generated complaints in the quotation processes in public procurement works in zone 3, through the quotation section in the public procurement system, to identify common errors. A mixed quantitative-qualitative approach was used to extract data, form matrices, and identify the most common complaints in zone 3. In addition, it was continued with a direct investigation through interviews to know the nonconformities of the bidders, according to the results obtained there are several frequent complaints in the provinces of zone 3, among these are: the planning error, the validity of documentation, and illegible documentation. This allowed to know how the state suppliers make known the nonconformities through claims in the National Public Procurement System platform